RELIGIOUS MODERATION IN COMPARATIVE MADHHAB CURRICULUM: A COMPARATIVE STUDY OF IAIN AMBON AND UIN ALAUDDIN MAKASSAR - Nurdin, Roswati; Musgamy, Awaliyah; Thalhah,; Ulath, Sanusi (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This study aims to examine how religious moderation values are manifested in the curriculum of Comparative Fiqh study programs at IAIN Ambon and UIN Alauddin Makassar. It focuses on understanding how these values are embedded in the program’s vision and implemented across four dimensions: Ideological, Document, Process, and Outcome. This qualitative research uses a case study approach, analyzing documents such as institutional strategic plans, program curricula, and reports from IAIN Ambon and UIN Alauddin Makassar. Interviews with faculty members and program administrators were conducted to gain insights into the practical implementation of religious moderation within the curriculum. The data was analyzed thematically. The study found that both institutions incorporate religious moderation values, including tolerance (tasamuh), compassion (tarahum), cooperation (taawun), and harmony (rukun) into their Comparative Fiqh curricula. These values are reflected in the institutions’ visions, emphasizing multiculturalism and universal Islamic principles. However, the integration of these values varies slightly between the two universities, influenced by their distinct local contexts. This research provides original insights into how religious moderation is integrated into Islamic higher education curricula in Indonesia, specifically within Comparative Fiqh programs. It bridges the gap between Islamic educational theory and practice, offering new empirical evidence on the incorporation of moderation in curriculum development. The findings have significant implications for Islamic education policy, curriculum design, and teacher training, encouraging the integration of religious moderation values in educational practices to foster inclusive, tolerant, and peaceful academic environments.